Analysis of the ukrainian construction market and raider captures in the context of economic security and social responsibility - MOHOLIVETS, Anton; LOKTIONOVA, Yana; GORBENKO, Sergii (Ways to Improve Construction Efficiency, 2024)
The article provides a comprehensive multi-faceted analysis of Ukrainian construction in the context of economic security of participants in investment and construction projects and social responsibility. Particular attention is paid to studying the impact of raider seizures on individual enterprises in the construction sector, participants in investment and construction projects and the construction industry itself. It is determined that raider seizures of enterprises and individual buildings are one of the most threatening phenomena for the stability of the business environment and the investment attractiveness of the sector, which in the pre-war period significantly affected the development of the construction sector and the stable work of construction participants. The paper examines key factors contributing to the emergence of raiding, including shortcomings in the legislative framework, corruption, insufficient efficiency of law enforcement agencies, and a low level of legal culture in society.The authors analyze current trends in the Ukrainian construction market, including its dynamics, major players, investment volumes, and regional specifics. The article focuses on critical problems, such as uneven development of regions, risks for small and medium-sized enterprises, and the impact of martial law and the country’s post-war reconstruction on the development of the construction industry.The study assumes the role of social responsibility in construction, in particular the need to comply with ethical norms, environmental standards, and take into account the needs of communities during the implementation of construction projects. Separately, the issues of state regulation of the industry, reforming the economic relations of property owners, including land plots, protecting the rights of property owners and tenants, and the necessary creation of mechanisms to prevent raiding attacks are highlighted.The conclusions of the article present recommendations for increasing the economic security of the construction market of Ukraine, in particular by improving legislation, implementing transparent management mechanisms, strengthening cooperation between the state, business and civil society, as well as stimulating socially responsible practices.